Trust in the Police in Rural China: a Comparison Between Villagers and Local Officials - Sun, Ivan Y. (Asian journal of criminology, 2019)
Although the past decade has witnessed the rise of studies on Chinese evaluations of the police, rural villagers’ assessments of the police remain under-researched. Drawing upon performance theory and survey data from China’s countryside, this study tested whether variations in satisfaction with government performance and life are linked to villagers’ and officials’ trust in county and local/town police. We found that villagers displayed lower levels of trust in the police than local officials. Higher satisfaction with government performance and integrity were associated with greater trust in county police among both villagers and officials. Villagers’ greater satisfaction with crime control and safety led to their stronger trust in both county and town police, but such satisfaction was not significantly related to officials’ trust in both levels of police forces. Rural residents’ generalized trust and particularized trust were associated with a greater likelihood of viewing the police as trustworthy. Meanwhile, female respondents, both villagers and officials, and higher-income officials were more likely to view the police as trustworthy. Directions for future research and policy are discussed.